DEVELOPMENT OF WAQF MANAGEMENT IN SAUDI ARABIA - Anisa Mawaddah; Siti Nurul Atiqah; Maryam Batubara (PT. Radja Intercontinental Publishing, 2024)
Waqf management in Muslim countries in the modern era is very diverse, both in terms of history, regulations, implementation and development. In this article, the author will explain how waqf is managed in Saudi Arabia, which will then be compared with Indonesia which is managed by the Indonesian Waqf Board. In practice, Indonesia is far behind several Muslim countries in managing waqf. This is due to the lack of political will from the government in managing waqf. In terms of regulations, waqf management only had its legal umbrella in 2004, even though the practice of waqf management has been going on for quite a long time.